2013
DOI: 10.1007/s00192-013-2078-y
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability when employing the IUGA/ICS classification system for complications related to prostheses and grafts in female pelvic floor surgery

Abstract: The IUGA/ICS mesh complication classification system has poor interobserver reliability. This trended downward with decreasing postgraduate level; however, we did not have sufficient statistical power to show an association when stratifying by all training levels. This highlights the complex nature of the classification system in its current form and its limitation for widespread clinical and research application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This is not a surprising finding since only 14% of the reports in the medical literature describing complications related to prosthesis/graft in pelvic surgery utilize this system . Gowda et al found that this classification has poor inter‐observer reliability, highlighting its complex nature. Efforts should be directed toward developing an improved system to ensure a widespread application in clinical and research fields.…”
Section: Discussionmentioning
confidence: 99%
“…This is not a surprising finding since only 14% of the reports in the medical literature describing complications related to prosthesis/graft in pelvic surgery utilize this system . Gowda et al found that this classification has poor inter‐observer reliability, highlighting its complex nature. Efforts should be directed toward developing an improved system to ensure a widespread application in clinical and research fields.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a mixed reaction to the IUGA/ICS classification system in the literature. Some studies have also found difficulty assigning a code to patients while others have been able to classify all or most . The interobserver reliability of the CTS system is poor but may be improved with optimized instruction .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also found difficulty assigning a code to patients while others have been able to classify all or most . The interobserver reliability of the CTS system is poor but may be improved with optimized instruction . Some studies have found good general applicability but recommend altering the system to include voiding dysfunction and de novo overactive bladder as there is currently no way to account for these common complications .…”
Section: Discussionmentioning
confidence: 99%